The Influence of Group Counseling with Cognitive Behavior Therapy to Improve Students' Self-Control: The Influence of Group Counseling with Cognitive Behavior Therapy to Improve Students' Self-Control - Bin Zain, Mawardi (Program Studi Bimbingan Konseling Islam Fakultas Dakwah dan Komunikasi Institut Agama Islam Hamzanwadi NW Pancor, 2024)
The purpose of this study was to see how muchinfluence group counseling using the Cognitive Behavior Therapy approach has in improving self-control of class XI IPS studentsat SMAN 2 Selong. This type of research is a quantitative experimental study using the one group pre-test post-test design type, namely by measuring the level of student self-control using a pre-test instrument which then obtaineda sample of 13 people, the 13 samples were then given treatment for 5 meetings, after that researcher measured again using the post-test instrument to seehow much increase in student self-control was produced after being given treatment. The results of this study indicate that there is a significant influence of group counseling using the Cognitive Behavior Therapy approach on improving self-control of class XI IPS students at SMAN 2 Selong. This can be seen in the results of the wilcoxon test data analysis, which obtained research results of 0.001 ≤ 0.05, meaning that there is a significant influence of groupcounseling using the Cognitive Behavior Therapy approach to improve students’ self-control. Keywords: Self-control, CBT